Pengaruh Pembelajaran Course Review Horay Berbantu Media Puzzle Huruf Terhadap Penguasaan Kosakata Siswa Pada Pembelajaran Bahasa Indonesia - Yohana, Nur Elia Putra; Purnanto, Arif Wiyat; Triana, Putri Meinita (Prosiding University Research Colloquium, 2021)
This study aims to determine the effect of Course Review Horay learning with the help of letter puzzle media on the vocabulary mastery of second grade students at SD Negeri Surodadi 3 Candimulyo. This study uses a pre-experimental design method type one group pretest-posttest design (single group initial test-posttest). The subjects in this study were saturated samples or total samples, namely by involving data collection carried out using the pretest posttest result assessment technique. The validation test of the pretest posttest results assessment instrument was carried out using expert validation. The instrument research test uses a validity test to test the results of the pretest posttest from the out-of-sample test results, while the instrument reliability test uses the Cronbach Alpha formula. Hypothesis test using wilcoxon test. Data analysis used non-parametric statistical techniques, namely the z-test or z-test with the help of the IBM SPSS Statistics 22 program. The results of the research data using the z-test or the Wilcoxon signed test, which obtained a Z value of -3.559 and an asymp sig value. (2-tailed) 0.001 is less than 5% (0.05). Based on the results of data analysis, the average pretest value was 52.5, while the posttest score was 77.5. From the results of the study, it can be concluded that the use of Course Review Horay learning aided by letter puzzle media has an effect on students’ vocabulary mastery.